Pentingnya Penerapan Pendidikan Karakter Dalam Pembelajaran - Alwazir Abdusshomad (Jurnal Asy-Syukriyyah, 2018)
Character education is a system that instill character values in the students, which contains the components of knowledge, individual awareness, determination and the willingness and action to implement the values, both of the one God, yourself, fellow human beings, the environment, and nation, so that will materialize perfect man. This is consistent with the educational objectives set out in the Basic Law No. 20 of 2003 which states that: "The national education serves to develop the ability and character development and a dignified civilization in the context of the intellectual life of the nation, aimed at developing the potential of students to become human the faith and fear of God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become citizens of a democratic and accountable.